Monocyte to HDL cholesterol ratio as a marker of the presence and severity of obstructive sleep apnea in hypertensive patients - Min Sun (Nature Portfolio, 2021)
Abstract This study aimed to investigate the correlation between monocyte to high-density lipoprotein cholesterol ratio (MHR) and obstructive sleep apnea (OSA) in patients with hypertension. A total of 246 hypertensive patients (67 controls, 65 mild, 51 moderate, and 63 severe OSA) were included. The relationship between MHR and OSA was analyzed. MHR correlated positively with apnea–hypopnea index (AHI), while negatively with mean SpO2 (P < 0.01). MHR was higher in OSA group than the control group (9.2 ± 2.6 vs. 10.8 ± 3.6, P < 0.001). Moreover, MHR in severe OSA group was the highest among all groups (9.2 ± 2.6, 10.2 ± 3.2, 10.4 ± 4.0, and 11.8 ± 3.4 in control, mild, moderate, and severe OSA group, respectively, P < 0.001). Logistic regression analysis demonstrated that MHR was an independent predictor of the presence of OSA (OR = 1.152, P < 0.01) and severe OSA (OR = 1.142, P < 0.01). Area under the curve of MHR was 0.634 (P < 0.05) and 0.660 (P < 0.05) for predicting OSA and severe OSA respectively in the ROC analysis. In conclusion, MHR increased with the severity of OSA. As a practical and cost-effective test, MHR was expected to be an available marker in evaluating OSA risk and severity in hypertensive patients.